Retelling Greek Tragedies: A Contemporary Trend in UK Drama - Cernadas-Lema, Carmen Gloria (Journal of Artistic Creation and Literary Research, 2025)
On 5 July 2015, the Greek referendum resulted in the rejection of the bailout conditions proposed by the European Union, the International Monetary Fund and the European Central Bank. This was a turning point for the EU, leading to speculation about a potential “Grexit”. In British society, this translated into a growing fascination with the Greeks, which did not escape the dramatic scene. The interest in Greek plays gave rise to the emergence of a new trend in UK drama: the retelling of Greek tragedies. This movement consists in the adaptation and re-elaboration of these ancient stories onto the contemporary stage. This paper delves into the origins, characteristics, and diverse perspectives of this recent trend in British drama. The sudden surge of interest in Greek tragedy in 2015, which has continued to flourish, is examined in the context of the UK’s socio-political landscape. This trend is a response to contemporary realities, making it a dynamic reflection of society. This study focuses on three noteworthy plays, Beautiful Evil Things (2022) by Deborah Pugh and George Mann, Iphigenia in Splott (2015) by Gary Owen, and Antigone (2022) by Inua Ellams. It uncovers common themes and distinct directorial techniques within this artistic movement.